2021
DOI: 10.1017/s0022377821000829
|View full text |Cite
|
Sign up to set email alerts
|

Radial distribution of the plasma potential in a cylindrical plasma column with a longitudinal magnetic field

Abstract: The possibility of controlling the electrostatic field distribution in plasma has yielded wide prospects for modern technologies. As a magnetic field primarily allows for creating electric fields in plasma, it serves as an additional obstacle for the current flow through a medium. In the present paper, an axially symmetric system is considered in which the magnetic field is directed along the axis and concentric electrodes are located at the ends. The electrodes are negatively biased. A model which solves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…It has, however, been recently shown that field penetration through the sheath and along field lines imposes a number of constraints on the achievable electric field (Gueroult, Rax & Fisch 2019 a ; Poulos 2019; Liziakin, Gavrikov & Smirnov 2020; Liziakin et al. 2021; Trotabas & Gueroult 2022). Meanwhile, studies in the last decade on rotating mirrors (Fetterman & Fisch 2008, 2010) and rotating tokamaks (Ochs & Fisch 2017; Rax et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has, however, been recently shown that field penetration through the sheath and along field lines imposes a number of constraints on the achievable electric field (Gueroult, Rax & Fisch 2019 a ; Poulos 2019; Liziakin, Gavrikov & Smirnov 2020; Liziakin et al. 2021; Trotabas & Gueroult 2022). Meanwhile, studies in the last decade on rotating mirrors (Fetterman & Fisch 2008, 2010) and rotating tokamaks (Ochs & Fisch 2017; Rax et al.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the potential of the electrodes can propagate along the lines, and the potential drop will occur in the transverse direction [ 11 ]. The question as to the extent to which such a transverse field can be controlled remains open [ 12 , 13 , 14 ]. However, there are studies that indicate a significant effect of thermal electron emissions from end electrodes on the potential distribution in the plasma column [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ключевым вопросом для плазменных методов, базирующихся на применении масс-фильтра Т. Окавы [3] и сепаратора В.П. Смирнова [4], является создание пространственного распределения электростатического потенциала с заданным профилем в замагниченной плазме [5,6]. Предполагается, что частицы сепарируемого вещества будут увлекаться скрещенными E × B полями и разделяться в пространстве согласно их массам.…”
Section: Introductionunclassified